Oxidative Rearrangements with Hypervalent Iodine Reagents - Singh, Fateh V.; Wirth, Thomas (Synthesis, 2013)
Hypervalent iodine chemistry is used as an important tool in synthetic and natural product chemistry. A number of hypervalent iodine reagents can be used to generate the functionalizations on various scaffolds by several chemical approaches including oxidation reactions, oxidative cyclization reactions, and rearrangements. Recently, these reagents have been employed to develop a variety of oxidative rearrangements. In this review article, various aspects of recently developed oxidative rearrangements using iodine(III) and iodine(V) reagents are described.1 Introduction2 Oxidative Rearrangements2.1 1,2-Aryl Group Migrations2.2 Hofmann Rearrangements2.2.1 Hofmann Rearrangements without Cyclizations2.2.2 Hofmann Rearrangements with Cyclizations2.3 Ring Contractions2.4 Ring Expansions2.5 Rearrangement of Tertiary Alcohols2.6 Wagner–Meerwein Rearrangements2.7 Domino Reactions3 Summary
Keywords: hypervalent iodine reagents; oxidative rearrangements; ring contractions; ring expansions